JAK POKAZAĆ LEK? OPAKOWANIA LEKÓW JAKO PŁASZCZYZNY WIZUALNE - Makowska, Magdalena (Acta Neophilologica, 2014)
Public space ever more often makes use of multimodal texts, combining linguistic and graphicpicture elements. The present article constitutes an attempt to present a linguistic analysis of multimodal texts based on the example of medication packaging. The research corpus consists of 50 medicine packages of nonprescription pain-relieving medications available in Poland, hence those whose purchase is independently decided upon by a customer. The economization of perception as well as the willingness to present a particular medicament in an attractive form for the recipient makes medicine packaging continually evolve, combining linguistic and picture elements. Simultaneously, those packages remain a unity which is coherent in functional, structural and semantic terms and that, in turn, entitles them to be treated in as semiotically arranged visual planes.